2010
DOI: 10.1111/j.1439-0531.2008.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oviductal Proteins on Structural and Functional Characteristics of Cryopreserved Sperm in Murrah Buffaloes

Abstract: The present study was undertaken to elucidate the effect of non-luteal oviductal proteins on sperm characteristics in Murrah buffaloes. Oviducts from healthy buffaloes were collected immediately after slaughter and the oestrous cycle phase was determined as either luteal or non-luteal based on ovarian morphology. Non-luteal oviducts (n = 80) were flushed from the isthmic end of the oviduct with PBS, fluid was centrifuged at 10,000 g at 4 degrees C for 20 min and then dialysed and clarified. The supernatant obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Resultados diferentes foram descritos por Iman et al [37], que observaram uma maior proporção de espermatozoides descongelados de búfa-los com membrana plasmática íntegra, revelada pelo teste hiposmótico, no grupo incubado com proteínas de oviduto em fase não lútea (32,6 %) que no grupo controle (27,0 %). …”
Section: Resultsunclassified
“…Resultados diferentes foram descritos por Iman et al [37], que observaram uma maior proporção de espermatozoides descongelados de búfa-los com membrana plasmática íntegra, revelada pelo teste hiposmótico, no grupo incubado com proteínas de oviduto em fase não lútea (32,6 %) que no grupo controle (27,0 %). …”
Section: Resultsunclassified
“…Around the time of ovulation, spermatozoa are progressively released towards the ampulla, the distal part of the oviduct, where they meet the oocyte [1]. Numerous in vitro studies have demonstrated that oviduct fluid (OF) proteins modulate sperm viability and mobility in cattle [4][5][6][7] and humans [8]. Furthermore, the effect of OF proteins on sperm varies according to the estrous cycle stage and the oviduct region from which the OF originates [5,6].…”
Section: Introductionmentioning
confidence: 99%